Plankton composition of Hakaluki Haor of Moulvibazar, Bangladesh - Bhuiyan, Mohammad Azmal Hossain; Mohid, Mahin; Islam, SAM Shariar; Kowser, Abu; Islam, Md Rasikul; Kakoly, Shahina Akter; Islam, Saiful; Khondker, Moniruzzaman (Dhaka University Journal of Biological Sciences, 2021)
In the present study, physicochemical and biological variables related to the water quality of Hakaluki Haor were studied. Three study stations viz. Bakshimul, Jalabeel and Dudhai were investigated because of an event of mass scale of dead fish and other aquatic organisms were reported. The stations had water depths from 2.74 - 5.13 m and Secchi Disc Transparency were 0.74 - 1.91 m. The air and water temperature among the three stations ranged from 28.2 - 30.4°C and 21.8 - 28.8°C, respectively. TDS ranged from 35 - 42 mg/l, while the electric conductivity of water showed 40 - 50 μS/cm. SRP, nitrate and SRS ranged from 10.68 - 12.32 μg/l, 0.116 - 0.122 mg/l and, 16.08 - 35.42 mg/l, respectively. The concentration of DO was very poor which ranged from 2.8 - 5.4 mg/l. In all the three studied stations, the free CO2 concentration was 0.096 mg/l. Chlorophyll-a value was moderate in all the three stations (ranged within 34.67 and 40.60 μg/l). The phaeopigment concentration was low and ranged from 1.51- 8.72 μg/l among the studied stations. Concentration of ammonia was much higher (1.03 - 1.72 mg/l) than the standard value for Bangladesh (0.5 mg/l). From this analysis, it is observed that during fish kill event the concentration of ammonia was higher with low DO content which might have resulted because of the decomposition of upper foliar parts of the rice plant due to the sudden inundation. Gross α and β counts were found to be 0.01 and 0.10 Bq/l in the Haor water at the time of fish kill. From the planktonic community, 16 phytoplanktons from green algae, 14 euglenoids, 5 diatoms, 5 dinoflagellates and 12 zooplankton species were recorded. A shift in the pH of the Haor water from acidic to alkaline might have occurred during the last 3 decades. A detailed limnological study covering the climatic seasons of Bangladesh has been recommended to be carried out for Hakaluki Haor. Dhaka Univ. J. Biol. Sci. 30(1): 69-78, 2021 (January)